Preservation of roasted and ground coffee during storage. Part 2: Bulk density and intergranular porosity - Corrêa, Paulo Cesar (2016)
The determination of physical properties is an important factor in the design of machinery and the scaling of post-harvest operations. The present study evaluates the influence of the level of roasting and the size of grinding on the physical properties of coffee during storage. The following physical properties were evaluated: true and bulk density, and intergranular porosity. Raw coffee beans (Coffea canephora and Coffea arabica), hulled and dried, were roasted to two different levels: medium light (SCAA#65) and moderately dark (SCAA#45). The beans were then grinded into three different sizes: fine (0.59 mm), medium (0.84 mm) and coarse (1.19 mm). An additional coffee lot was kept whole. Following grinding, samples were stored at two different temperatures (10 and 30 ºC) and analyzed after five different storage durations (0, 30, 60, 120 and 180 days). The medium light roast had higher values for each of the measured physical properties. Finely ground samples had higher true and bulk densities, and porosities. It is concluded that the size of grinding, level of roasting and duration of storage significantly affect the physical properties of coffee.